Effect of Investments on Cash flow of Manufacturing Firms Listed at the Nairobi Securities Exchange - Musembi, Damaris Mutindi; Sporta, Fred (International Journal of Finance Research, 2023)
The researcher in this study sought to establish the factors that affect cash flow in manufacturing firms in Kenya. The study was guided by the following specific objectives,to establish how investments affect cash flow in manufacturing firms listed in the Nairobi stock exchange, to find out how inventory controls affect cash flow   in manufacturing firms listed in the Nairobi stock exchange, to determine how profitability affect cash flow in manufacturing firms listed in the Nairobi stock exchange. The researcher used descriptive research design to describe the factors affecting cash flow in manufacturing firms listed in the Nairobi stock exchange. A firm should be able to generate enough cash flows from its operations. If a firm is not able to cover its current liabilities with cash generated from operations, it will have cash challenges in financing its operations. A cash flow ratio of oneshow that the firm has healthy cash flows and a ratio of less than one shows that the firm does not have enough cash flows to finance its operations. The study covered a period of five years from 2012 to 2017.The methodology for the study was descriptive research design. The study employed population census as the listed firms were very few for the researcher to employ sampling. The listed firms were nine. Analyzed data was presented using figures and tables. The study findings revealed that there is a positive relationship between cash flows and investments as measured by net capital expenditure, profitability as measured by return on assets. There is a negative relationship between cash flows and inventory control as measured by inventory turnover. The study also established that there is a positive relationship between cash flows and profitability of a firm as measured by return on Assets (ROA).cash flows in all the firms have the same trend expect for Eveready East African ltd. The study concluded that manufacturing firms should exercise inventory control, invest wisely and also manage profitability of assets to ensure that the firm has enough cash flows to fund its operations